2009
DOI: 10.1007/s10734-009-9230-0
|View full text |Cite
|
Sign up to set email alerts
|

The Canada Research Chairs Program: the good, the bad, and the ugly

Abstract: Drawing on 60 qualitative interviews with Canada research chairs (CRCs), we explore their careers in context. We develop a model to understand the intersection of individual and institutional factors that shape the everyday experiences of the CRCs. The model shows the dialectical relationship between faculty identity, research, relations with colleagues and students, and institutional practices and structures. We classify individuals' experiences as ''good,'' ''bad,'' or ''ugly.'' The interviews show that whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…For example, in the 2006-2007 academic year, only 13% of Social Science and Humanities Research Council granting funds were awarded to full-time academics in the humanities, education, and social science disciplines, despite the fact that these disciplines account for roughly 49% of all full-time Canadian academics (CAUT 2010a , 44). Similar trends are found in relation to the Canadian Foundation for Innovation (CAUT 2010a , 45) and the Canada Research Chair granting programmes (Grant and Drakich 2010 ) . Generally speaking, federal government support for academic research in the social sciences and humanities is 3.5 times less than for research in the natural sciences, engineering, and health fi elds (Statistics Canada 2010 ) .…”
Section: Disciplinesupporting
confidence: 75%
See 1 more Smart Citation
“…For example, in the 2006-2007 academic year, only 13% of Social Science and Humanities Research Council granting funds were awarded to full-time academics in the humanities, education, and social science disciplines, despite the fact that these disciplines account for roughly 49% of all full-time Canadian academics (CAUT 2010a , 44). Similar trends are found in relation to the Canadian Foundation for Innovation (CAUT 2010a , 45) and the Canada Research Chair granting programmes (Grant and Drakich 2010 ) . Generally speaking, federal government support for academic research in the social sciences and humanities is 3.5 times less than for research in the natural sciences, engineering, and health fi elds (Statistics Canada 2010 ) .…”
Section: Disciplinesupporting
confidence: 75%
“…There is a considerable literature on discipline differences in higher education, and a number of studies of Canadian higher education have noted important differences in the availability of research funding, support for infrastructure, and remuneration patterns by discipline (Grant and Drakich 2010 ;CAUT 2010a ) . For example, in the 2006-2007 academic year, only 13% of Social Science and Humanities Research Council granting funds were awarded to full-time academics in the humanities, education, and social science disciplines, despite the fact that these disciplines account for roughly 49% of all full-time Canadian academics (CAUT 2010a , 44).…”
Section: Disciplinementioning
confidence: 99%
“…While one can hypothesize as to the reason for this continued resistance to management by non-academic forces, specifically looking at the strong tradition of institutional autonomy in the Canadian context, further study is required in order to understand how this autonomy has been maintained in Canada while having been sacrificed in part or in whole in other jurisdictions, particularly the other Anglophone countries, as exemplified in Slaughter and Leslie's account of academic capitalism in Canada, the United States, the UK, and Australia (Slaughter & Leslie, 1997). Further, recent scholarship (Metcalfe, 2010) suggests that trends of academic capitalism are more prevalent in Canada than previously articulated, and evidence of commercialization and its mechanisms encourages further research to explore how academic autonomy may be shifting (Grant & Drakich, 2010). In addition, the CAP responses require further examination along a number of trajectories, particularly in terms of different institutional types (research-focused vs. teaching-focused), disciplines, professional ranks, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, questions about the long-range sustainability of these positions (Dufour, 2010) and the insertion of administrative preferences into faculty hiring decisions have surfaced. Furthermore, as study by Grant and Drakich (2010) found, although many CRCs have had positive experiences, some have found that their departmental relationships are strained and the extent of their rewards are misunderstood by their peers, leaving them to feel like 'the rich kid on the block' (p. 33). As departmental colleagues were less involved in the hire, they may rebuff or resent an administrative insertion of a 'star' faculty member into their unit.…”
Section: Crc Programmementioning
confidence: 99%